Separatism against the state: the case of Catalonia - Yuskiv, Khrystyna (Східноєвропейський національний університет імені Лесі Українки, 2019)
The primary purpose of the article is to correlate a predominant position of some regions with the intensity of separatist movements there. Two tendencies of peripheral separatism have been discovered in Europe. The role of the European continent is confirmed in representing different independent regional and interregional organisations, i.e. through the Assembly of European Regions comprising roughly 300 regional entities. A brief analysis has been made of several regions facing the most evident separatist tendencies and ethnic turbulence. Coincidence factor and prosperity syndrome as accelerant of separatist tendencies have been noted in the Western and Eastern parts of Europe, pointing out different surroundings and the same triggering motivation. And finally, some of most effective instruments to withstand separatist pressure, backed by external powers in proxy-war environments, have been suggested.The article is devoted to the study of the problem of separatism in Spain – a country with the hottest cell manifestation of this phenomenon in modern Europe. Among the 19 autonomous regions of the country during the last time, the separatist movement has gained particular activity in Catalonia. At the heart of the study is the study of the historical peculiarities of the development of separatism in Catalonia and the reasons that led to the emergence of separatist sentiments in this autonomy. In the course of the study, the main causes of Catalan separatism – economic, ethno-political and political – were considered, an analysis of the intensity of the influence of each of these reasons, the degree of their significance as being conducive to separatism. The dominant role in shaping the manifestations of separatism in Catalonia is due to economic factors, in particular, the reluctance to finance the more backward regions, and in the form and intensity of its manifestation, Catalan separatism is regarded as active, secessional. The possible consequences of the intensification of separatism in Catalonia for Spain and Europe as a whole have been identified. This situation is a serious threat to the unity of the kingdom, as it can cause a chain reaction and stir up separatism in other autonomous communities where it is in a moderate or passive state, especially in the Basque Country and Galicia, Andalusia, Aragon, Asturias, Cantabria, Castile, Leoni, Balearic the islands The activation of the separatist movement in Catalonia may also intensify the movement for the separation of certain regions from other European countries and create a threat to Europe's unity. Considered measures to combat separatism in Catalonia, in particular, the effectiveness of combating the active separatism of force methods.
Keywords: separatism; methods of counteracting separatism; Catalonia; secession; causes of separatism; consequences of separatism; 323.173 (913.4)